Pengembangan Media Pembelajaran Matematika Melalui Video Pembelajaran pada Mata Kuliah Teori Bilangan - Nur'aini Muhassanah; Ambar Winarni; Afifah Hayati (ARITHMETIC: Academic Journal of Math, 2022)
Developing a video for learning mathematics in the Number Theory course as the purpose of this research. This needs to be done to help students understand the material during online learning. The development procedure in this R&D research is based on the ADDIE product development model (analyze, design, development, implementation, evaluation). The stages of this research are limited to the development and trial stages. Furthermore, at the trial stage, one class is carried out to take the Number Theory course in the odd semester for the Academic Year 2021-2022. The results of this study are (1) several learning videos have been formed in the Number Theory course based on sub-materials; (2) the learning video media is declared feasible based on the results of the assessment from a team of experts consisting of two validators, the results obtained from four aspects, namely the material aspect, language and image aspects, presentation aspects, and finally the display aspect with a final average score of 75 with appropriate criteria; and (3) the results of the trial obtained the results of the completeness test, the average score was 75.28 and the comparative test results obtained the average value. The mean of completeness of the experimental class and the control class were 75.28 and 60.28. The value of the experimental class is better than the control class.